2009
DOI: 10.1016/j.ejcts.2009.07.021
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the type of resection on survival in patients with N1 non-small-cell lung cancers

Abstract: Those who had PN or BL had a higher survival rate, which was statistically insignificant. Further studies are required to determine whether or not the type of resection should be changed as a result of N1 only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…[1,4,5] In addition, a number of studies have examined the factors related to long-term survival. [6][7][8] However, the incidence and the mechanism of circulatory and respiratory failure in the long-term is unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,4,5] In addition, a number of studies have examined the factors related to long-term survival. [6][7][8] However, the incidence and the mechanism of circulatory and respiratory failure in the long-term is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…[1,4,7,9] However, the long-term implications of these risk factors are not well-known. Long-term survival after pneumonectomy is primarily associated with the stage of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…They are mainly based on statistical modelling, including Kaplan-Meier curves, hierarchical statistical models, logistic and Cox regressions [4], [5], [6], [7]. Other approaches make use of logistic regression models to construct the so-called scoring tables.…”
Section: Related Workmentioning
confidence: 99%
“…Create S N (F k ) from S N by selecting only attributes from F k ; 3 Eliminate examples containing missing values from S N (F k ); 4 Train base learner h k on S N (F k ); 5 Calculate GMean value G k on S N (F k ) achieved by h k ; 6 …”
Section: B Creating Ensemble Classifiermentioning
confidence: 99%
“…Lobectomy is the gold standard, but some studies have suggested better survival after pneumonectomy. 15 – 18 The aim of this single-institution study was to evaluate the prognostic factors in resected N1 disease, focusing on node descriptors (with the current and new IASLC proposed TNM staging systems) and surgical procedure.…”
Section: Introductionmentioning
confidence: 99%